Assessment of the Rockburst Proneness in Hard Rock Coal Mines - S. P. Singh (International Conference on Ground Control in Mining, 1986)
Rockburst is a sudden manifestation of the release of elastic strain energy stored in the rock. Therefore the tendency of the rock to burst should depend upon its ability to accumulate elastic strain energy. The use of Burst Proneness Index as a simple and reliable indicator to recognize the burst prone situations in the mines has been advocated in this study. The Burst Proneness Index exhibited a strong dependence upon the brittleness, compressional and shear wave velocities and the point load strength index. It was also observed that the Burst Proneness Index increases with the increase in the strain energy per unit volume, c ressive strength and the modulus of rigidity of the rocks. In addition, important causes and the measures to alleviate rockbursts have been outlined in this paper.